N6-adenosine-methyltransferase MTA70-like participates antiviral responses in Nicotiana benthamiana - Wang, Haijuan; Zhang, Tianyi; Xu, Jiaxin; Sun, Zhenqi; Wu, Zhaoran; Zhang, Baolong; Zhao, Qianqian; Yang, Xiangdong; Zhao, Mingmin (Frontiers in Microbiology, 2026)
IntroductionPrevious studies have shown that m6A methylation has a certain regulatory role in the replication of human viruses and plant viruses. Particularly, the m6A methylation in the host endogenous gene significantly decreased after the infection of potato virus Y (PVY).MethodsHere, we cloned and characterized N6-adenosine-methyltransferase MTA70-like (ToMTA70) from tomato. The ToMTA70 was constructed into the pMDC32 binary vector. To create the ToMTA70 mutant, sequence of the MTA70 superfamily domain (493-653) with PDS and GUS sequences, respectively. The effect of the ToMTA70 on viral accumulation was studied using an Agrobacterium-mediated transient expression assay.ResultsA conserved MT-A70 superfamily domain in ToMTA70 was identified by encoding sequence and structural analyses, which indicating ToMTA70 might involve in m6A methylation. The transient expression of ToMTA70 inhibited viral accumulation of PVY. When the conserved domain of MTA70 super family was replaced by PDS and GUS (ToMTA70-PDS or ToMTA70-GUS), the PVY infection was increased in plants comparing with the control. However, transiently expression of ToMTA70 did not show any influence on TVMV and TMV infection.DiscussionThis suggests that ToMTA70 participate in plant antiviral responses of PVY, which can be applied for engineering the anti-viral strategy.